Spatio-temporal distribution of microalgae producing chlorophyll and carotenoid pigments in Bali Strait, Indonesia - ANNA FAUZIAH; DIETRIECH G BENGEN; MUJIZAT KAWAROE; HEFNI EFFENDI; MAJARIANA KRISANTI (Society for Indonesian Biodiversity, 2019)
Fauziah A, Bengen DG, Kawaroe M, Effendi H, Krisanti M. 2019. Spatio-temporal distribution of microalgae producing chlorophyll and carotenoid pigments in Bali Strait, Indonesia. Biodiversitas 20: 61-67. The Bali Strait waters become a place for various development activities that connect Java Island and Bali Island so that it is thought to have an impact in the life of microalgae that play an important role in the wealth of their water resources. This study aims to explore the spatiotemporal distribution of marine microalgae, which has the potential to produce chlorophyll and carotenoid pigments, as well as their relationship with the environmental characteristics of the Bali Strait waters. The research was conducted at the 5 stations in the morning, midday and afternoon. The data obtained were analyzed using Principal component analysis (PCA) and Correspondence analysis (CA). The results showed that chlorophyll-a, chlorophyll-b and carotenoid were mostly contained by the species Chaetoceros gracilis, Tripos lunula at station 5 (Pang-pang Bay) in the morning, midday and afternoon, and contained by the species Fragilariopsis cylindrus, Thalassiothrix fravenfeldii at station 3 (Ketapang-Gilimanuk ferriage) in the midday and afternoon. Spatially, salinity, ammonia, nitrate, and chlorophyll-a have significantly different values between stations, while temporally the content of chlorophyll-b and carotenoid are influenced by time (in the morning, midday and afternoon).